Traffic-related air pollution and allergic disease: an update in the context of global urbanization. Issue 2 (April 2017) - Carlsten, Christopher; Rider, Christopher F.
Abstract : Purpose of review: The review aims to give an update on the literature around traffic-related air pollution (TRAP) and allergic disease in the context of global urbanization, as the most populous countries in the world face severe TRAP exposure challenges. Recent findings: As research continues to show that gene–environment interactions and epigenetics contribute to the TRAP–allergy link, evidence around the links to climate change grows. Greenspace may provide a buffer to adverse effects of traffic on health, overall, but pose risks in terms of allergic disease. Summary: The link between traffic-related pollution and allergy continues to strengthen, in terms of supportive observational findings and mechanistic studies. Levels of TRAP across the world, particularly in Asia, continue to dramatically exceed acceptable levels, suggesting that the related adverse health consequences will accelerate. This could be counterbalanced by primary emission control and urban planning. Attention to combined effects of TRAP and allergen exposure is critical to avoiding misleading inferences drawn though examination only of isolated factors.